A Simple One-Pot Synthesis of 4-Phenyl-3-Oxo Pyrimido[4,5-b] Quinolines and their Biocidal Studies - Nandha Kumar, R.; Suresh, T.; Mohan, P.S. (Asian Journal of Chemistry, 2010)
A convenient one-pot synthesis of pyrimido [4,5-b] quinolines 3a-e has been achieved from 2-chloro-3-formyl quinolines 1 and N-phenylurea 2. All the synthesized compounds have been biologically screened for their antibacterial and antifungal activities.